Skrining Fitokimia, Uji Toksisitas dan Uji Peredaman Radikal DPPH Ekstrak Daun Gelinggang (Cassia alata L): Phytochemical Screening, Toxicity Test and DPPH Radical Scavenging Test of Cassia alata L (Gelinggang) Leaves Extract - Izkia Mawaddah; Erwin E; Chairul Saleh (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2020)
Cassia alata L. (Gelinggang) one of the plants known as medicinal plants, especially for the treatment of skin diseases. The purpose of this study was to determine the type of secondary metabolites using phytochemical tests, toxicity with the BSLT method and antioxidant properties against DPPH radicals from the extract of the Gelinggang leaves. The results of the study showed extracts of Gelinggang leaves containing alkaloids, triterpenoids, steroids, and quinones. Based on the results of toxicity and antioxidant tests showed that Gelinggang leaves extract was very toxic to Artemia salina shrimp and it was a strong antioxidant against DPPH radicals with LC50 and IC50 were 28.84 ppm and 73.57 ppm, respectively. Keywords: Gelinggang, Cassia alata L., toxicity, antioxidants, DPPH